Analisis Kesesuaian Penggunaan Lahan Terhadap Rencana Detail Tata Ruang (RDTR) di Kecamatan Pati Kabupaten Pati - Tia Junia Hidayah; Muh. Sholeh (JPIG (Jurnal Pendidikan dan Ilmu Geografi), 2026)
Pati District's urban growth is typified by a growing population, which influences changes in land use and the need for more space. The purpose of this study is to examine land use in 2024 and determine whether it is appropriate for the Pati District Detailed Spatial Plan (RDTR). By using an overlay technique between the current land use map and the RDTR zoning map, the research methodology employs a Geographic Information System (GIS)-based spatial analysis approach. The land suitability evaluation shows that 77.37% of the area is classified as suitable for the RDTR, while 22.63% is not. This finding indicates that the dynamics of existing land use are not fully aligned with the RDTR directives. Therefore, it is necessary to strengthen control of spatial use through periodic monitoring and evaluation, as well as the implementation of control instruments such as the Transfer of Development Rights (TDR) to maintain harmony between land use and spatial plans.